HUBUNGAN PENGETAHUAN DAN SIKAP WUS DENGAN MINAT MELAKUKAN PEMERIKSAAN IVA TEST DI WILAYAH KERJA PUSKESMAS MELAK TAHUN 2021 - Yustina Titin; Jasmawati Jasmawati; Lukman Nulhakim (Jurnal Ilmu Kebidanan, 2023)
Preliminary: Cervical cancer is the fourth most common type of cancer experienced by women. The IVA test is a method of screening cervical cancer lesions that is easy, simple and feasible. Analyzing the relationship between WUS knowledge and attitude factors with WUS interest in the working area of the Melak Health Center carrying out the IVA test. Method: This study uses a quantitative approach, analytical observational with a cross sectional design. The research sample amounted to 105 WUS who met the inclusion criteria. Result: The results showed that statistical analysis with Somer's D test showed that there was a relationship between knowledge (p-value = 0.000) and attitude (p-value = 0.001) with WUS interest in carrying out the IVA test. Conclusion: There is relationship between knowledge and attitude with iterest of IVA Test examination. The Puskesmas is expected to increase the target, coverage and education regarding the IVA test for WUS in their working area. Keywords: Reproductive age woman, Knowledge, Attitude, IVA test